Brazilian Amazonian microorganisms: A sustainable alternative for plant development - Monyck Jeane dos Santos Lopes; Aline Figueiredo Cardoso; Moacyr Bernardino Dias-Filho; Ely Simone Cajueiro Gurgel; Gisele Barata da Silva (AIMS Microbiology)
Plant growth-promoting microorganisms (PGPM) are a sustainable and promising alternative to enhance agricultural production. The Brazilian Amazon, and its mostly unexplored biodiversity, have great potential for identifying and isolating beneficial microorganisms to develop sustainable protocols for plant production with less environmental damage and to meet the increasing demand for food production. Thus, this study aimed to synthesize the findings over the last decade on microorganisms from the Amazon biome that promote plant growth while also addressing the challenges and prospects of this biotechnology. Rhizobacteria (PGPR) and fungi native to the Amazon have been shown to enhance the development of various crops, spanning agriculture and forestry, including palm cultivation and forage crops. The potential of PGPM in the Brazilian Amazon discussed throughout this review highlights the importance of further research in this region. Amazon PGPM is promising for use in the inoculant industry, which would contribute to the agricultural production of diverse crops, reduce costs, minimize the use of chemical inputs, mitigate adverse environmental impacts, and support the conservation of the Amazon biome. Furthermore, the advancement of knowledge in this region holds a great potential, thus offering access to different strains for the formulation of new inoculants that can, in a more sustainable manner, enhance the productivity of various crops, thereby promoting global food security.